Comparative Effectiveness of Pamphlet and Video Media in Enhancing Breast Self-Examination Knowledge Among High School Students - Anggie Widyaswara; Melani Putri; Mila Sartika; Yulidian Nurpratiwi (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: Adolescence represents a critical developmental stage during which health-related knowledge and preventive behaviours begin to form. Limited awareness of breast health and breast self-examination (BSE) among adolescent girls may reduce opportunities for early detection of breast abnormalities. Educational interventions delivered through accessible media may play an important role in improving adolescents’ understanding of BSE. Objective: This study aimed to evaluate the effectiveness of health education delivered through pamphlets and video media on the level of knowledge regarding breast self-examination among female adolescents. Methods: A quantitative study with a quasi-experimental design using a two-group pretest–posttest approach was conducted at SMAN 3 Tambun Selatan. The study population comprised 598 female students, of whom 592 participated using a total sampling technique. Knowledge of breast self-examination was assessed using a structured questionnaire administered before and after the educational intervention. Data were analysed using the Wilcoxon nonparametric test. Results: The findings demonstrated a statistically significant improvement in adolescents’ knowledge of breast self-examination following education delivered through pamphlets and video media (p < 0.001). Prior to the intervention, most participants showed limited concern for breast health. Post-intervention results indicated increased awareness and understanding of the importance of regular breast self-examination. Conclusion: Health education using pamphlets and video media is effective in enhancing adolescents’ knowledge of breast self-examination. Integrating structured and media-based educational strategies within school health programmes may strengthen preventive health behaviours and promote early breast health awareness among adolescents.